THE PROCESSES OF FAMILY AND INDIVIDUAL SOCIALIZATION IN THE INFORMATION SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the transformation of social relations between the family and the individual within the context of the information society. It analyzes the family’s role in the process of socialization, the influence of digital communication tools and media on the formation of social values and behavioral patterns, and the dual impact of social networks and globalization on family relations and youth education. The study concludes that there is a growing need to improve socialization mechanisms in today’s information-driven society to ensure balanced personal and social development.